Signalling Pathways in Development and Human Disease: A Drosophila Wing Perspective - Molnar, Cristina; Resnik-Docampo, Martín; Organista, María F.; Martín, Mercedes; Hevia, Covadonga F.; Celis, Jose F. de (IntechOpen, 2011)
None